2011
DOI: 10.5194/hessd-8-1059-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneity of soil carbon pools and fluxes in a channelized and a restored floodplain section (Thur River, Switzerland)

Abstract: Due to their spatial complexity and dynamic nature, floodplains provide a wide range of ecosystem functions. However, because of flow regulation, many riverine floodplains have lost their characteristic heterogeneity. Restoration of floodplain habitats and the rehabilitation of key ecosystem functions has therefore become a major goal of environmental policy. Many important ecosystem functions are linked to organic carbon (C) dynamics in riparian soils. The fundamental understanding of the factors that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 49 publications
3
64
0
Order By: Relevance
“…This interpretation would explain the delayed response of soil respiration to flood events, as well as the trend in CO 2 emission in relation to flood frequency (Table 3). Similar to the trend observed in the present investigation, a study conducted in the Thur River watershed (Switzerland) found higher rates of CO 2 emission in riparian buffers along flood-affected sections of the river compared to riparian areas near channelized sections of the river (Samaritani et al, 2011).…”
Section: Controlling Factors Of Soil Respirationsupporting
confidence: 85%
“…This interpretation would explain the delayed response of soil respiration to flood events, as well as the trend in CO 2 emission in relation to flood frequency (Table 3). Similar to the trend observed in the present investigation, a study conducted in the Thur River watershed (Switzerland) found higher rates of CO 2 emission in riparian buffers along flood-affected sections of the river compared to riparian areas near channelized sections of the river (Samaritani et al, 2011).…”
Section: Controlling Factors Of Soil Respirationsupporting
confidence: 85%
“…The values of Q 10 coefficients reported for Fluvisols are higher than the value obtained for the urban meadow (site B-2.98). In Switzerland, Samaritani et al [26] obtained Q 10 values of 3.6 for grass, 3.4 for pasture and 3.2 for mixed forest. Awasthi et al [27] report Q 10 values in a range from 2.5 to 5.0 for mixed Fluvisols, Cambisols, Rigosols and Luvisols in Nepal.…”
Section: Temporal Variability Of Soil Co 2 Fluxmentioning
confidence: 98%
“…3b). Samaritani et al (2011) have shown that frequent disturbance by flood pulses of a floodplain forest led to high heterogeneity with temporarily and locally increased C pools and soil respiration but also higher CH 4 fluxes.…”
Section: Methanementioning
confidence: 99%